Activated carbon as well as preparation method and application thereof

By mixing the main coal and auxiliary materials for preparation, and using Fe2O3 catalytic activation, the pore structure of activated carbon is expanded, the problem of low molasses value of activated carbon is solved, and the adsorption capacity of macromolecular substances is improved. It is suitable for decolorization treatment of sugar production or beverage industry.

CN119706837APending Publication Date: 2025-03-28SHENHUA XINJIANG ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411743181.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The value of activated carbon molasses prepared by the prior art is low, resulting in weak adsorption capacity of macromolecular substances, limiting its application in the decolorization process of sugar production or beverage industry.

Method used

By mixing the main coal and the auxiliary material, powdering, molding, oxidation reaction, carbonization and activation are carried out in turn. The physical activation method is used and the Fe2O3 in the auxiliary material is used as the catalytic active site to expand the micropore structure of the activated carbon to the mesoporous or mesoporous structure, thereby increasing the molasses value.

Benefits of technology

The molasses value of activated carbon has been significantly improved, the adsorption capacity of macromolecular substances has been enhanced, and the demand for decolorization treatment in the sugar production industry or beverage industry has been met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706837A_ABST
    Figure CN119706837A_ABST
Patent Text Reader

Abstract

The invention provides activated carbon as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing main coal and auxiliary materials, and sequentially performing powdering, forming, oxidation reaction, carbonization and activation to obtain the activated carbon, wherein the main coal comprises the following components in percentage by weight: 1 to 5 weight percent of water, 2 to 5 weight percent of ash, 33 to 39 weight percent of volatile component, 50 to 65 weight percent of fixed carbon, 0.2 to 0.5 weight percent of total sulfur and inevitable impurities; the auxiliary material is prepared from the following components in percentage by weight: 2 to 4 weight percent of water, 10 to 15 weight percent of ash, 30 to 40 weight percent of volatile component, 20 to 35 weight percent of Fe2O3 and inevitable impurities. The main coal and the auxiliary materials with the specific components are selected as the preparation raw materials of the activated carbon, so that the activated carbon with a relatively high molasses value can be obtained, and the activated carbon has relatively high adsorption capacity on macromolecular substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of activated carbon preparation, and in particular, relates to activated carbon, a preparation method and application thereof. Background Art

[0002] In recent years, based on my country's abundant coal resources and the increasing market demand for activated carbon, coal-based activated carbon has become the mainstream development trend. Activated carbon has a developed pore structure inside, which determines its excellent adsorption performance, and can be widely used in water purification, food and pharmaceutical decolorization, national defense and other industries. According to the shape of activated carbon, it can be divided into powdered activated carbon, columnar activated carbon and briquette activated carbon. Among them, although the development of briquette activated carbon is a little later, the preparation technology of coal-based briquette activated carbon has entered a mature stage.

[0003] Generally, the preparation process of activated carbon mainly includes pulverizing, molding, carbonization and activation steps. The purpose of the pulverizing step is to grind the raw coal into coal powder of uniform qualified particle size; the purpose of the molding step is to first press the obtained coal powder into blocks and then crush it to form a briquette with a certain particle size and high strength; the purpose of the carbonization step is to treat the briquette with low temperature dry distillation under air-tight conditions to obtain a carbonized material with a preliminary pore structure; the purpose of the activation step is to cool the carbonized material to about 70°C and then enter the activation furnace for activation to improve the porosity and adsorption effect of the activated carbon. This process requires the control of parameters such as the activation temperature of each furnace layer, water vapor flow rate and discharge time.

[0004] However, the coal-based compressed activated carbon produced by the conventional technology generally has more developed micropores, and has a better adsorption effect on small molecular pollutants, and is suitable for adsorbing small molecular substances with a pore size of less than 2nm, but its molasses value is low, and its adsorption capacity for macromolecular substances is weak, which greatly limits the application of coal-based compressed activated carbon in the decolorization process of the sugar industry or beverage industry. Therefore, it is necessary to provide a new preparation method of activated carbon, which can effectively improve the above problems. Summary of the invention

[0005] The main purpose of the present invention is to provide an activated carbon, a preparation method and application thereof, so as to solve the problem that the activated carbon prepared by the prior art has a low molasses value.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a method for preparing activated carbon, comprising: mixing main coal and auxiliary materials, and sequentially carrying out pulverizing, molding, oxidation reaction, carbonization and activation to obtain activated carbon; wherein, the composition of the main coal is as follows, by weight percentage: 1-5wt% of moisture, 2-5wt% of ash, 33-39wt% of volatile matter, 50-65wt% of fixed carbon, 0.2-0.5wt% of total sulfur and inevitable impurities; the composition of the auxiliary materials is as follows, by weight percentage: 2-4wt% of moisture, 10-15wt% of ash, 30-40wt% of volatile matter, 20-35wt% of Fe2O3 and inevitable impurities.

[0007] Furthermore, the bonding index of the main coal is 3-15, and the bonding index of the auxiliary material is 80-88.

[0008] Furthermore, the coke slag characteristics of the main coal are ≤3, and the coke slag characteristics of the auxiliary materials are ≥6.

[0009] Furthermore, the softening point of the auxiliary material is 159-175°C.

[0010] Furthermore, the weight ratio of the main coal to the auxiliary material is (80-97):(3-20), preferably (85-95):(5-15).

[0011] Furthermore, physical activation is used for activation; preferably, the activator used for activation is selected from one or more of water vapor, carbon dioxide, air or flue gas; preferably, the amount of the activator is 2 to 3 kg per kilogram of carbonized material; preferably, the activation treatment temperature is 920 to 960°C, and the treatment time is 4 to 8 hours.

[0012] Furthermore, during the oxidation reaction, the amount of oxygen used is 5 to 40 mL per kilogram of the total weight of the main coal and auxiliary materials; preferably, the reaction temperature during the oxidation reaction is 80 to 300°C, and the reaction time is 2 to 3 hours; preferably, the reaction temperature during the carbonization process is 300 to 600°C, and the reaction time is 0.5 to 3.0 hours.

[0013] Furthermore, the passing rate of the powder after milling on a 325-mesh circular vibrating screen is ≥70%, and the passing rate of the 180-mesh circular vibrating screen is ≥90%.

[0014] Furthermore, the strength of the molded material is ≥93%.

[0015] In order to achieve the above object, according to one aspect of the present invention, there is provided an activated carbon, which is prepared by the above preparation method provided in the present application.

[0016] According to another aspect of the present invention, there is provided an application of the above-mentioned activated carbon provided in the present application in a decolorization process in the sugar or beverage industry.

[0017] By applying the technical solution of the present invention, the present application selects the main coal and auxiliary materials of the above-mentioned specific components as raw materials for preparing activated carbon, and can obtain an activated carbon with a higher molasses value, which has a strong adsorption capacity for macromolecular substances. In particular, the Fe2O3 in the auxiliary materials can be used as a catalytic active site in the subsequent activation process to promote the formation of micropores (pore size 0.1-2.0nm) of the product, while further accelerating the erosion and pore expansion of the material by the activator during activation, thereby expanding the microporous structure in the product to a medium or mesoporous structure with a larger pore size (pore size 2-50nm), so that it can meet the high molasses value requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1 A flow chart of a method for preparing activated carbon in one embodiment of the present invention is shown. DETAILED DESCRIPTION

[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0021] As described in the background technology section of the present invention, the activated carbon prepared by the prior art has the problem of low molasses value. In order to solve this problem, the present invention provides a method for preparing activated carbon, such as Figure 1 As shown, the preparation method includes: mixing main coal and auxiliary materials, and performing pulverization, molding, oxidation reaction, carbonization and activation in sequence to obtain activated carbon; wherein, the composition of the main coal is as follows by weight percentage: 1-5wt% moisture, 2-5wt% ash, 33-39wt% volatile matter, 50-65wt% fixed carbon, 0.2-0.5wt% total sulfur and inevitable impurities (such as iron, arsenic, phosphorus); the composition of the auxiliary materials is as follows by weight percentage: 2-4wt% moisture, 10-15wt% ash, 30-40wt% volatile matter, 20-35wt% Fe2O3 and inevitable impurities (such as arsenic, phosphorus).

[0022] The present application selects the main coal and auxiliary materials of the above-mentioned specific components as raw materials for the preparation of activated carbon, and can obtain an activated carbon with a high molasses value, which has a strong adsorption capacity for macromolecular substances. In particular, the Fe2O3 in the auxiliary materials can be used as a catalytic active site in the subsequent activation process to promote the formation of micropores (pore size 0.1-2.0nm) of the product, while further accelerating the erosion and pore expansion of the material by the activator during activation, thereby expanding the microporous structure in the product to a medium or mesoporous structure with a larger pore size (pore size 2-50nm), so that it can meet the high molasses value requirements.

[0023] It should be additionally added that, in the above-mentioned main coal of the present application, the ash content includes but is not limited to ferric oxide, aluminum oxide, potassium oxide, and calcium oxide, and the volatile matter includes but is not limited to N element, H element, C element, and S element. In the above-mentioned auxiliary materials, the ash content includes but is not limited to aluminum oxide, potassium oxide, and calcium oxide, and the volatile matter includes but is not limited to N element, H element, C element, and S element.

[0024] In order to make the product have better strength performance on the basis of meeting the above-mentioned high molasses value requirement, it is preferred that the bonding index of the main coal is 3-15, and the bonding index of the auxiliary material is 80-88. Based on this, the strength of the activated carbon can be increased from 90% to 93%. More preferably, the slag characteristics of the main coal are ≤3, and the slag characteristics of the auxiliary material are ≥6. The slag characteristics of the main coal and the auxiliary material include but are not limited to the above ranges, and limiting them within the above ranges is conducive to the molding of activated carbon.

[0025] In a preferred embodiment, the softening point of the auxiliary material for preparing high molasses value activated carbon is 159-175° C. Compared with other ranges, limiting the softening point of the auxiliary material to the above temperature range is conducive to improving the hardness and grindability of the raw material, thereby facilitating the molding and briquetting of activated carbon, and further helping to obtain activated carbon with higher strength.

[0026] In a preferred embodiment, the weight ratio of the main coal to the auxiliary material is (80-97):(3-20). Compared with other ranges, limiting the weight ratio of the main coal to the auxiliary material within the above range is conducive to better synergistic effect of the main coal and the auxiliary material, and the advantages of the main coal and the auxiliary material can be effectively exerted to a greater extent, which is conducive to further obtaining high-strength, high-molasses value activated carbon on the basis of lower cost. If the weight ratio of the main coal to the auxiliary material is higher than this range, the mesopore porosity in the obtained activated carbon product is reduced; and if the weight ratio of the main coal to the auxiliary material is lower than the above range, it will cause the pore wall between the formed activated carbon mesopores and the adjacent mesopores to melt, thereby generating macroporous channels that cannot function. More preferably, the weight ratio of the main coal to the auxiliary material is (85-95):(5-15).

[0027] In a preferred embodiment, the above activation is carried out by a physical activation method, which can make the carbon compounds present in the activated carbon decompose more fully, so that they escape through the surface of the product to form micropores on the surface of the product. Moreover, the Fe2O3 in the above auxiliary material serves as a catalytic active site, which can accelerate the erosion and pore expansion of the main coal by the activator during this activation process, thereby playing a beneficial effect of expanding the above micropores into mesopores with larger pore sizes. In the actual operation process, after the activation is completed, the activated material is cooled to 50-70°C to obtain the above activated carbon. Preferably, the activator in the activation process includes but is not limited to one or more of water vapor, carbon dioxide, air and flue gas. Based on this, the above pore structure formation process of the present application is more stable and the product structure uniformity is better. In order to further improve the activation efficiency, it is more preferred that the amount of the activator is 2-3kg per kilogram of material after the carbonization reaction. In order to further improve the stability of the activation, the temperature during the activation process is 920-960°C and the time is 4-8h.

[0028] In order to further improve the strength performance of the product, in a preferred embodiment, during the oxidation reaction, the amount of oxygen used is 5 to 40 mL per kilogram of the mixed material of the main coal and the auxiliary materials. In a preferred embodiment, the reaction temperature during the oxidation reaction is 80 to 300 ° C, and the reaction time is 2 to 3 hours. The reaction temperature during the carbonization reaction is 300 to 600 ° C, and the reaction time is 0.5 to 3.0 hours. Compared with other ranges, limiting the reaction conditions of the oxidation and carbonization processes to the above range is conducive to the initial formation of a small amount of graphitized structure and a large amount of non-graphitized structure inside the carbonized material. The non-graphitized structure is dominant, which is convenient for more effectively facilitating the formation of the subsequent pore structure of the product, and then providing a carbon precursor for the activation process. More preferably, those skilled in the art can first perform low-temperature dry distillation on the material after the oxidation reaction under air isolation conditions, that is, carbonize the material.

[0029] In a preferred embodiment, a person skilled in the art can use a coal mill to carry out the above-mentioned pulverizing of a mixture of main coal and auxiliary materials under the conditions of a mill outlet temperature of 60 to 70°C and a roller loading force of 8 to 10 MPa. The fineness of the powder after pulverizing is ≥70% for a 325-mesh circular vibrating screen pass rate and ≥90% for a 180-mesh circular vibrating screen pass rate. A person skilled in the art can also use a coal powder binder-free molding technology to carry out the above-mentioned molding. Specifically, a person skilled in the art can first mold the coal powder after pulverizing in a briquetting machine with a roller current of 300±10A to obtain a black pillow-shaped material with a length of 50 to 60 mm, a width of 20 to 30 mm, and a height of 10 to 20 mm. After molding, a person skilled in the art can continue to crush the material into irregular shapes of 2 to 10 mm, and the strength of the material after molding is ≥93%. Compared with powders of other particle sizes and molding materials of other strengths, this material has a more suitable particle size and briquetting strength, which is conducive to the full reaction of the mixed material in the subsequent oxidation, carbonization and activation processes, thereby preparing activated carbon with a higher molasses value.

[0030] Another aspect of the present application provides an activated carbon, which is obtained by the above preparation method. Based on the above reasons, the activated carbon prepared by the above method not only has the advantages of high iodine value, high strength, low ash content, etc., but also has a high molasses value of ≥220 mg·g -1 .

[0031] Another aspect of the present application also provides an application of the above-mentioned activated carbon in the decolorization process of the sugar industry or beverage industry. The activated carbon prepared by the above-mentioned method provided by the present application not only has the advantages of high iodine value, high strength, low ash content, etc., but also has a high molasses value of ≥220mg·g -1 In this way, the activated carbon can have a stronger adsorption capacity for macromolecular substances in the subsequent decolorization process of the sugar industry or beverage industry.

[0032] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0033] Example 1

[0034] The main coal comes from Hami, Xinjiang. Among them, by weight percentage, the main coal contains 1.53wt% moisture, 2.46wt% ash, 0.4wt% total sulfur, 37.5wt% volatile matter, 58wt% fixed carbon and the balance of inevitable impurities, the coke slag characteristic is 3, and the bonding index is 5. By weight percentage, the auxiliary materials contain 2.78wt% moisture, 11.5wt% ash, 31.54wt% volatile matter, 30wt% Fe2O3 and the balance of inevitable impurities, the softening point is 165℃, and the coke slag characteristic is 6.

[0035] The above main coal and auxiliary materials are mixed in a weight ratio of 90:10, and pulverizing, molding, oxidation reaction, carbonization reaction and activation are carried out in sequence. Among them, the particle size of the pulverized powder is 70% for a 325-mesh circular vibrating screen pass rate, and 92% for a 180-mesh circular vibrating screen pass rate. The reaction temperature during the oxidation reaction is 300°C, the time is 2.5h, and the amount of oxygen used is 40mL (based on the total weight of each kilogram of main coal and auxiliary materials). The reaction temperature of the carbonization reaction is 580°C and the time is 3h. The temperature during the activation process is 960°C and the time is 4h. The activator is water vapor, and the amount of the activator is 3kg (based on each kilogram of material after the carbonization reaction).

[0036] Example 2

[0037] The main coal comes from Qitai County, Changji District, Xinjiang. Among them, by weight percentage, the main coal contains 4.55wt% moisture, 4.01wt% ash, 0.2wt% total sulfur, 35.71wt% volatile matter, 55wt% fixed carbon and the balance of inevitable impurities, the coke slag characteristic is 3, and the bonding index is 12. By weight percentage, the auxiliary materials contain 3.90wt% moisture, 14.01wt% ash, 38.19wt% volatile matter, 23wt% Fe2O3 and the balance of inevitable impurities, the softening point is 172℃, and the coke slag characteristic is 6.

[0038] The above main coal and auxiliary materials are mixed in a weight ratio of 85:15, and powder making, molding, oxidation reaction, carbonization reaction and activation are carried out in sequence. Among them, the particle size of the powder making is 70% through the 325-mesh circular vibrating screen, and the pass rate of the 180-mesh circular vibrating screen is 91%. The reaction temperature during the oxidation reaction is 285°C, the time is 2.5h, and the amount of oxygen used is 20mL (based on the total weight of each kilogram of main coal and auxiliary materials). The reaction temperature of the carbonization reaction is 580°C and the time is 1.5h. The temperature during the activation process is 930°C and the time is 7h. The activator is water vapor, and the amount of the activator is 2.3kg (based on each kilogram of material after the carbonization reaction).

[0039] Example 3

[0040] The main coal comes from Hutubi County, Changji District, Xinjiang. Among them, by weight percentage, the main coal contains 2.73wt% moisture, 2.91wt% ash, 0.3wt% total sulfur, 39.0wt% volatile matter, 55.06wt% fixed carbon and the balance of inevitable impurities, the coke slag characteristic is 2, and the bonding index is 7. By weight percentage, the auxiliary materials contain 3.01wt% moisture, 12.3wt% ash, 33.05wt% volatile matter, 28wt% Fe2O3 and the balance of inevitable impurities, the softening point is 171℃, and the coke slag characteristic is 6.

[0041] The above main coal and auxiliary materials are mixed in a weight ratio of 95:5, and powder making, molding, oxidation reaction, carbonization reaction and activation reaction are carried out in sequence. Among them, the particle size of powder making is 70% through a 325-mesh circular vibrating screen, and 92% through a 180-mesh circular vibrating screen. The reaction temperature during the oxidation reaction is 288°C, the time is 2h, and the amount of oxygen used is 40mL (based on the total weight of each kilogram of main coal and auxiliary materials). The reaction temperature of the carbonization reaction is 600°C and the time is 2.5h. The temperature during the activation process is 950°C and the time is 5h. The activator is water vapor, and the amount of the activator is 2.8kg (based on each kilogram of material after the carbonization reaction).

[0042] Example 4

[0043] The main coal comes from Jimusar County, Changji District, Xinjiang. Among them, by weight percentage, the main coal contains 3.28wt% moisture, 3.11wt% ash, 0.5wt% total sulfur, 38.6wt% volatile matter, 54.51wt% fixed carbon and the balance of inevitable impurities, the coke slag characteristic is 3, and the bonding index is 10. By weight percentage, the auxiliary materials contain 3.37wt% moisture, 13.65wt% ash, 35.21wt% volatile matter, 25wt% Fe2O3 and the balance of inevitable impurities, the softening point is 175℃, and the coke slag characteristic is 6.

[0044] The above main coal and auxiliary materials are mixed in a weight ratio of 97:3, and powder making, molding, oxidation reaction, carbonization reaction and activation are carried out in sequence. Among them, the particle size of powder making is 70% through a 325-mesh circular vibrating screen, and 90% through a 180-mesh circular vibrating screen. The reaction temperature during the oxidation reaction is 280°C, the time is 2.8h, and the amount of oxygen used is 30mL (based on the total weight of each kilogram of main coal and auxiliary materials). The reaction temperature of the carbonization reaction is 585°C and the time is 2h. The temperature during the activation process is 940°C and the time is 6h. The activator is water vapor, and the amount of the activator is 2.5kg (based on each kilogram of material after the carbonization reaction).

[0045] Example 5

[0046] The main coal comes from Toksun County, Turpan, Xinjiang. Among them, by weight percentage, the main coal contains 5wt% moisture, 5wt% ash, 0.3wt% total sulfur, 39wt% volatile matter, 50.7wt% fixed carbon and the balance of inevitable impurities, the coke slag characteristic is 3, and the bonding index is 15. By weight percentage, the auxiliary materials contain 4wt% moisture, 15wt% ash, 40wt% volatile matter, 20wt% Fe2O3 and the balance of inevitable impurities, the softening point is 159℃, and the coke slag characteristic is 6.

[0047] The above main coal and auxiliary materials are mixed in a weight ratio of 80:20, and pulverizing, molding, oxidation reaction, carbonization reaction and activation reaction are carried out in sequence. Among them, the particle size of the pulverized powder is 70% through a 325-mesh circular vibrating screen, and 90% through a 180-mesh circular vibrating screen. The reaction temperature during the oxidation reaction is 275°C, the time is 2h, and the amount of oxygen used is 10mL (based on the total weight of each kilogram of main coal and auxiliary materials). The reaction temperature of the carbonization reaction is 590°C and the time is 40min. The temperature during the activation process is 920°C and the time is 8h. The activator is water vapor, and the amount of the activator is 2kg (based on each kilogram of material after the carbonization reaction).

[0048] Comparative Example 1

[0049] The only difference from Example 1 is that the above-mentioned auxiliary materials are not added.

[0050] Comparative Example 2

[0051] The only difference from Example 1 is that the main coal and the auxiliary material are mixed in a weight ratio of 98:2.

[0052] Comparative Example 3

[0053] The only difference from Example 1 is that the main coal and the auxiliary material are mixed in a weight ratio of 75:25.

[0054] Performance characterization: The activated carbon in the above embodiments and comparative examples was subjected to performance tests, and the test results are shown in Table 1 below.

[0055] Table 1

[0056]

[0057] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0058] From the test results of Examples 1, 2, and 3 and Comparative Example 1, it can be found that when the activated carbon obtained by the preparation method of the present application is compared with the activated carbon prepared without adding auxiliary materials, its molasses value is ≥220, the strength is ≥96.5%, and the comprehensive performance is better, exceeding the index requirements of the decolorization fields such as the sugar industry and beverage industry at home and abroad, and has a strong decolorization ability for macromolecular substances in the adsorbent, which can better meet the market demand.

[0059] From the test results of Examples 1, 2, 3, 4, 5 and Comparative Examples 2 and 3, it can be found that when the activated carbon obtained by the preparation method of the present application is used, especially when the weight ratio of the main coal to the auxiliary material is within the range of (80-97): (3-20) (for example, 90:10 in Example 1, 85:15 in Example 2, 95:5 in Example 3, 97:3 in Example 4, and 80:20 in Example 5), the prepared activated carbon has a higher molasses value and caramel decolorization rate, and has higher strength and better comprehensive performance. In particular, when the weight ratio of the preferred main coal to the auxiliary material is within the range of (85-95): (5-15) (for example, 90:10 in Example 1, 85:15 in Example 2, and 95:5 in Example 3), the adsorption capacity of the activated carbon is better and the comprehensive performance is stronger. However, when the weight ratio of the main coal to the auxiliary material is outside the range of (80-97):(3-20) (for example, 98:2 in Comparative Example 2 and 75:25 in Comparative Example 3), the adsorption performance of the activated carbon is poor.

[0060] In summary, the high molasses value activated carbon prepared by the present application has a molasses decolorization power of ≥220 and a strength of ≥96.5%, which exceeds the index requirements of the decolorization fields such as the sugar industry and the beverage industry at home and abroad, has a strong decolorization ability for macromolecular substances in the adsorbent, and can better meet market demand.

[0061] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing activated carbon, characterized in that: include: The main coal and the auxiliary materials are mixed and successively subjected to pulverization, molding, oxidation reaction, carbonization and activation to obtain the activated carbon; wherein, The composition of the main coal is as follows, in terms of weight percentage: 1-5wt% moisture, 2-5wt% ash, 33-39wt% volatile matter, 50-65wt% fixed carbon, 0.2-0.5wt% total sulfur and unavoidable impurities; Calculated by weight percentage, the components of the auxiliary material are as follows: 2-4wt% of moisture, 10-15wt% of ash, 30-40wt% of volatile matter, 20-35wt% of Fe2O3 and inevitable impurities.

2. The method for preparing activated carbon according to claim 1, characterized in that: The bonding index of the main coal is 3-15, and the bonding index of the auxiliary material is 80-88.

3. The method for preparing activated carbon according to claim 1 or 2, characterized in that: The coke slag characteristics of the main coal are ≤3, and the coke slag characteristics of the auxiliary material are ≥6.

4. The method for preparing activated carbon according to any one of claims 1 to 3, characterized in that: The softening point of the auxiliary material is 159-175°C.

5. The method for preparing activated carbon according to any one of claims 1 to 4, characterized in that: The weight ratio of the main coal to the auxiliary material is (80-97):(3-20), preferably (85-95):(5-15).

6. The method for preparing activated carbon according to claim 1, characterized in that: The activation is carried out by a physical activation method; Preferably, the activating agent used in the activation is selected from one or more of water vapor, carbon dioxide, air and flue gas; Preferably, the amount of the activator is 2-3 kg per kilogram of the carbonized material; Preferably, the activation treatment temperature is 920-960° C., and the treatment time is 4-8 hours.

7. The method for preparing activated carbon according to claim 1, characterized in that: During the oxidation reaction, the amount of oxygen used is 5 to 40 mL per kilogram of the total weight of the main coal and the auxiliary materials; Preferably, the reaction temperature during the oxidation reaction is 80-300°C and the reaction time is 2-3h; Preferably, the reaction temperature in the carbonization process is 300-600° C., and the reaction time is 0.5-3.0 h.

8. The method for preparing activated carbon according to claim 1, characterized in that: The particle size of the powder after milling has a passing rate of ≥70% on a 325-mesh circular vibrating screen and a passing rate of ≥90% on a 180-mesh circular vibrating screen; Preferably, the strength of the molded material is ≥ 93%.

9. An activated carbon, characterized in that The activated carbon is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the activated carbon according to claim 9 in a decolorization process in the sugar or beverage industry.